Conservation biology in Asia - McNeely, Jeffrey A.; Society for Conservation Biology. Asia Section; Resources Himalaya Foundation (Nepal) (Kathmandu : Society for Conservation Biology Asia Section : Resources Himalaya Foundation, 2006)
Contributed papers from a seminar held in Kathmandu in Nov. 2005.
Includes bibliographical references and index.
Keywords: Conservation biology -- Asia -- Congresses